Adequate surgical margins for oral cancer: A Taiwan cancer registry national database analysis. (August 2021) - Lin, Mei-Chun; Leu, Yi-Shing; Chiang, Chun-Ju; Ko, Jenq-Yuh; Wang, Cheng-Ping; Yang, Tsung-Lin; Chen, Tseng-Cheng; Chen, Chun-Nan; Chen, Hsin-Lin; Liao, Chun-Ta; Tsai, Sen-Tien; Lin, Jin-Ching; et al.
Highlights: Adequate surgical margin for OSCC needs to be re-evaluated. The study enrolled 15, 654 patients with OSCC from the TCR database. Advanced N stage and positive margin are major risk factors for poor CSS and OS. Surgical margins <4 mm and <5 mm predict poor CSS and OS, respectively. Abstract: Background: Margin status and lymph node metastasis are the most important prognostic factors for oral cancers. However, while adequate surgical resection is crucial for local control and prognosis, the definition of clear margins has long been a subject of debate. In this study, we analyzed data from a nationwide population-based cancer registry database and evaluated the impact of surgical margins on cancer-specific survival (CSS) and overall survival (OS) as well as the optimal cutoff of adequate surgical margins. Methods: This analysis included all cases of oral cancer diagnosed from 2011 to 2017 that were reported to the Taiwan Cancer Registry database. The staging system was converted from American Joint Committee on Cancer (AJCC) version 7 to AJCC version 8. Kaplan–Meier analysis and Cox proportional-hazards regression were performed to identify covariates that were significantly associated with CSS and OS. Results: Between 2011 and 2017, 15, 654 of a total of 36, 091 cases diagnosed with oral cancers were included in the final analyses. Advanced N stage, positive margins, and advanced T stage are the leading risk factors for poor CSS and OS. When surgical margins were subdivided into 1-mm intervals from 5 mm to positive margin, we found that surgical margins <4 mm and <5 mm predict poor CSS and OS, respectively. Conclusions: This is the first nationwide, population-based cohort to revisit the question of the adequate surgical margins for oral cancers. We conclude that surgical margins ≥4 mm and ≥5 mm are adequate for good CSS and OS, respectively.